Exploring the Hypocholesterolemic Potential of a Fucus vesiculosus Extract: Omic Insights into Molecular Mechanisms at the Intestinal Level - Rebeca, André (2024)
High blood cholesterol levels are a major risk factor for cardiovascular diseases. A purified aqueous extract of Fucus vesiculosus, rich in phlorotannins and peptides, has been described for its potential to inhibit cholesterol biosynthesis and intestinal absorption. In this work, the effect of this extract on intestinal cells' metabolites and proteins was analysed to gain a deeper understanding of its mode of action on lipids' metabolism, particularly concerning the absorption and transport of exogenous cholesterol. Caco-2 cells, differentiated into enterocytes, were exposed to the extract, and analysed by untargeted metabolomics and proteomics. The results of the metabolomic analysis showed statistically significant differences in glutathione content of cells exposed to the extract compared to control cells, along with an increased expression of fatty acid amides in exposed cells. A proteomic analysis showed an increased expression in cells exposed to the extract compared to control cells of FAB1 and NPC1, proteins known to be involved in lipid metabolism and transport. To the extent of our knowledge, this study is the first use of untargeted metabolomics and a proteomic analysis to investigate the effects of F. vesiculosus on differentiated Caco-2 cells, offering insights into the molecular mechanism of the extract’s compounds on intestinal cells.